Perbandingan Data Mining Menggunakan Metode Decision Tree C4.5 dan Naïve Bayes dalam Penentuan Penjurusan Siswa (Studi Kasus : SMA PGRI 109 Kota Tangerang) - Maar, Halili (Prodi Teknik Informatika Universitas Pasir Pengaraian, 2025)
Student majors are carried out in high school in accordance with the interests and carried out by students registering with the aim to provide opportunities for students to develop competencies, competencies, and academic abilities in a collection of scientific subjects. In this study, the data used are data on the results of the entrance examinations held at school for students who have passed the entrance examination at SMA PGRI 109 Kota Tangerang. In this study using the Decision Tree C4.5 Algorithm and the Naive Bayes Algorithm by using two data mining classification algorithms, to find out which algorithm gets a model or value with a higher verification result.